2022
DOI: 10.1002/deo2.109
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence in colonoscopy: A review on the current status

Abstract: Artificial intelligence has become an increasingly hot topic in the last several years, and it has also gained its way into the medical field. In recent years, the application of artificial intelligence in the gastroenterology field has been of increasing interest, particularly in the colonoscopy setting. Novel technologies such as deep neural networks have enabled real‐time computer‐aided polyp detection and diagnosis during colonoscopy. This might lead to increased performance of endoscopists as well as pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…CADe involves real-time image analysis to detect polyps, with the aim of increasing the ADR and decreasing the AMR [ 7 , 25 ]. Studies have shown the ADR to be inversely related to the risk of interval colorectal cancer and mortality [ 23 , 26 ], and a US study of more than 300,000 colonoscopies reported a 3% decrease in the risk of interval colorectal cancer for every 1% increase in the ADR [ 27 ]. CADe systems have enabled the real-time AI-aided detection of adenomas with higher sensitivity than the average endoscopist [ 28 ].…”
Section: Ai In Colonoscopymentioning
confidence: 99%
See 2 more Smart Citations
“…CADe involves real-time image analysis to detect polyps, with the aim of increasing the ADR and decreasing the AMR [ 7 , 25 ]. Studies have shown the ADR to be inversely related to the risk of interval colorectal cancer and mortality [ 23 , 26 ], and a US study of more than 300,000 colonoscopies reported a 3% decrease in the risk of interval colorectal cancer for every 1% increase in the ADR [ 27 ]. CADe systems have enabled the real-time AI-aided detection of adenomas with higher sensitivity than the average endoscopist [ 28 ].…”
Section: Ai In Colonoscopymentioning
confidence: 99%
“…Studies have reported a minimum number of 100 to 200 colonoscopy procedures to reach technical competence [ 66 68 ], with an average training period of 4 years in the United Kingdom [ 69 ]. Thus, there is bound to be great variation amongst endoscopists in terms of skill [ 26 ]. A US study reported differential ADR rates of 7.4% to 52.5% between endoscopists [ 27 ].…”
Section: Future Directions For Ai In Colonoscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Images collected during colonoscopy, a common colorectal cancer screening method, can be used to train artificial intelligence (AI), machine learning (ML), and deep learning (DL) systems for computer-aided diagnosis (CADx) [ 10 ]. By analysing and interpreting the colonoscopy images, these diagnostic tools may facilitate a more precise diagnosis of colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%